Pengaruh Independensi dan Etika Auditor terhadap Kualitas Audit Dengan Fee Audit sebagai Variabel Moderasi - Sunarno, Sunarno; Indriyanto, Erwin (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of auditor independence and ethics on audit quality, with audit fees as a moderating variable, in Public Accounting Firms (KAP) located in South Jakarta. The research is motivated by the importance of maintaining audit quality as a form of accountability and public trust in the accounting profession. Auditor independence is often considered a key factor in ensuring the objectivity of audit results, while auditor ethics serve as a moral foundation for delivering high-quality audits. However, differing opinions exist regarding the extent to which these two factors truly impact audit quality, especially considering the role of audit fees, which often become a sensitive issue in the auditor-client relationship. This study employs a quantitative approach using Partial Least Squares (PLS) analysis with the SmartPLS software. The population includes all auditors working in Public Accounting Firms in South Jakarta, with a saturated sampling technique applied so that all members of the population are included in the sample. The results show that auditor independence has a significant positive effect on audit quality, meaning that higher levels of independence lead to better audit quality. On the other hand, auditor ethics do not significantly affect audit quality, indicating that ethical considerations are not always explicitly reflected in audit outcomes. Additionally, audit fees are found to moderate the relationship between independence and audit quality but do not moderate the relationship between auditor ethics and audit quality.